REKONSTRUKSI SISTEM PENDIDIKAN ISLAM DALAM PANDANGAN KH. ABDUR RAHMAN WAHID - Ady Ashari; Nasrul Amin (Universitas Yudharta Pasuruan, 2019)
Islamic education system is very important in an Islamic educational institution, because this system will color Rahman Wahid Islamic education in the future. In the post-independence era of Islamic education system in Indonesia is still chaotic, therefore KH. Abdur Rahman Wahid who we used to know as Gus Dur contributed his thoughts on the good Islamic education system in Indonesia. Therefore the need for reconstruction within the body of Islamic education in Indonesia. This article examines Gus Dur's ideas in the Islamic education system and uses an analytical content approach based on Gus Dur's works.